Optimizing ionic conduction properties in PMMA/PLA-LiBOB gel polymer electrolytes with addition of SiO2 nanofillers - N. M., Khan; N. F., Mazuki; M. Z., Kufian; Ahmad Salihin, Samsudin (Institute for Ionics, 2025)
In this research, varying silica nanofllers (SiO2) compositions ranging from 2 to 12 wt.% were introduced into PMMA/ PLA-20% LiBOB gel polymer electrolyte (GPE) systems. Comprehensive characterization techniques, including FTIR, XRD, TGA, EIS, and TNM, were employed to assess the structural, thermal, and ionic conduction properties. FTIR analysis revealed subtle shifts and intensity changes at several key peaks, indicating molecular interactions within the GPE. XRD analysis showed a notable reduction in crystallinity, particularly up to 6 wt.% SiO2, suggesting that the nanofllers promoted complexation and increased the amorphous regions within the GPEs. TGA confrmed that the 6 wt.% SiO2 sample exhibited the least mass loss, indicating superior thermal stability. The ionic conductivity reached a maximum of 2.19× 10–3 S cm−1 for samples containing up to 6 wt.% SiO2, correlating with the lowest activation energy of~0.021 eV. This enhancement is attributed to the role of SiO2 as a bridge that facilitates improved ion complexation with the polar polymer chains. Additionally, all GPE systems exhibited Arrhenius behavior, with R2 values close to 1. The ionic transport studies indicated that the parameters ɳ, µ, and D signifcantly infuence the ionic conductivity behavior. The highest conducting sample was selected for TNM testing, which revealed a notably lithium-ion transference number of 0.48. This fnding underscores the practical viability of this composition for lithium-ion batteries, promising enhanced electrochemical performance.